Pengembangan Model Pembelajaran Kooperatif Jigsaw pada Materi Karya Ilmiah Kelas XI MA Al-Ma’tuq dalam Meningkatkan Kualitas Pemahaman Siswa - Ikhsan Abdul Aziz; Iis Ristiani (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This study discusses the development of a jigsaw-type cooperative learning model in class XI Scientific Work material. This research is applied to Indonesian Language learning and is carried out at Madrasah 'Aliyah Al-Ma'tuq. The problem discussed was about the lack of understanding of students on the use of previous learning models that have been used in Scientific Work materials. This research is expected to confirm the usefulness of the jigsaw-type cooperative learning model for class XI Scientific Work material. This research uses a qualitative method with interview techniques. The results of this study suggest that jigsaw cooperative learning in the Scientific Work material of grade XI MA Al-Ma'tuq is proven to make the learning material easier for students to understand.